Analisis Perbedaan Kegiatan Ekstrakurikuler di SD Negeri 02 Sukahati dan SD Islam Sedunia - Shalaisa Saputri; Afa Zahra; Sefhiana Andara (PT. ALHAFI BERKAH INDONESIA, 2023)
The quality of extracurricular activities at an educational institution is a marker of the overall quality of education at that institution. The fierce competition in the extracurricular realm in the world of education recently shows that schools need to make maximum efforts to be able to manage educational activities effectively and of high quality. Managers of educational institutions are expected to be able to guide their students to achieve achievements in various fields in various competitions held for students, both in academic and non-academic aspects. This research was conducted with the first aim of being able to explain the planning of extracurricular activities at SDN Sukahati 02 and SD Islam Sedunia, secondly being able to explain the implementation of extracurricular activities at SDN Sukahati 02 and SD Islam Sedunia, thirdly being able to explain the process of evaluating extracurricular activities at SDN Sukahati 02 and SD Islam Worldwide, and fourthly analyzing the differences in extracurricular activities at SDN Sukahati 02 and SD Islam Sedunia. The methodology used in this research is a qualitative descriptive method. Data collection in this research was obtained from interviews, observations and documentation. The results of this research are that there are differences in terms of management of extracurricular activities carried out in state elementary schools and private elementary schools, which are also influenced by various obstacles, challenges and constraints.